Enhancing Students' Interest through Culturally Responsive Problem-Based Biology Learning - Fabilka Aura Pirnika; Abd Hakim Laenggeng; Muhammad Irfan Hafid (Equator Science Journal, 2025)
This classroom action research aimed to improve students’ learning interest, participation, and achievement in biology through the application of Culturally Responsive Problem-Based Learning (CRPBL) supported by flipped classroom strategies. The study was conducted in two cycles with 32 students from class XI at SMA Negeri 7 Palu. Data were collected using questionnaires, observation sheets, and achievement tests, and analyzed through percentages, mastery, and N-Gain. The findings indicate substantial improvements across all dimensions. Students’ interest rose from 62.5% (moderate) in Cycle I to 85.3% (high) in Cycle II, while participation increased from 38% (low) to 81% (high). Academic achievement also improved, with mean scores rising from 80.0 to 86.2 and mastery from 76% to 91%. The N-Gain of 0.48 reflected medium improvement. These results provide strong evidence that CRPBL with flipped classroom strategies can effectively enhance students’ engagement and performance in biology. Beyond its effectiveness, this study addresses the scarcity of empirical research integrating culturally responsive teaching, problem-based learning, and flipped classroom approaches in Indonesian secondary schools, thereby filling a critical gap in contextualized biology education. The findings imply that teachers can adopt CRPBL to design more meaningful lessons, while schools may implement it to align with the Merdeka Curriculum. Future studies are recommended to apply CRPBL in varied contexts with longer durations to further validate its effectiveness.